Algorithm of machine creation using the mechanism of articulated disjunction - Zinko, Roman; Hlobchak, Mykhailo; Beshley, Andiy; Pitrenko, Oleksiy (Видавництво Львівської політехніки, 2022)
Problem statement. Any methodology is based on knowledge about the problem. The fullness and orderliness of the base determine further volumes and possible options for implementing the methodology. Purpose. To analyze the existing ways of machine creations and propose the new effective algorithm of machine creation using the mechanism of articulated disjunction. Considering the research structure and improvement of the informational and program technologies, changes to the traditional methodology of machine creation are made. The existing paradigm: parametric and functional performance of the machine, the design of which is improved based on existing machines, is a modification of predecessors' parametric and functional performance. Proposed paradigm: parametric and functional performance of the new machine, improved based on the subject area of technical solutions, methods of design and operational conditions more precisely coincide with the technological process to realize what they are called. Proposed hypothesis: there are such methodologies of design that provide an opportunity to provide rational productivity within existing operational conditions. Methodology. Morphological space is used to form qualitative features of the created machine. The peculiarity of the proposed methodology is that the set of features of the created machine also contains subsets of processes and phenomena in which the machine is involved. This allows assessing the compliance of the process in which the machine is involved and the machine operation processes. Findings (results). The algorithm of machine creation using the mechanism of articulated disjunction is proposed. It allows the creation of the new construction at a given sequence of stages to improve at every step in a given direction based on the determined criteria. Originality (novelty). Method of articulated disjunction, which is based on the principle of formation of the set of necessary properties of the structural elements of the machine based on a given primary criterion of machine efficiency. The essence of the method of articulated disjunction is that the sample of elements that have common features and properties is reformulated based on a given criterion. The proposed method provides an opportunity to determine the advantages of one structure described by various factors, in comparison with others, based on the criterion set. Practical value. The algorithm of synthesis and improvement of existing machines allows for determining their main quality features in the initial stages of the design of machines.
Keywords: knowledge base; the algorithm of machine creation; mechanism of articular disjunction; morphological space; quality features of the machine; graphs of constructive schemes of machines